2018
DOI: 10.1289/ehp2622
|View full text |Cite
|
Sign up to set email alerts
|

Drilling and Production Activity Related to Unconventional Gas Development and Severity of Preterm Birth

Abstract: Background:Studies of unconventional gas development (UGD) and preterm birth (PTB) have not presented risk estimates by well development phase or trimester.Objective:We examined phase and trimester-specific associations between UGD activity and PTB.Methods:We conducted a case–control study of women with singleton births in the Barnett Shale area, Texas, from 30 November 2010 to 29 November 2012. We individually age- and race/ethnicity-matched five controls to each PTB case (n=13,328) and truncated controls’ ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 50 publications
5
61
0
Order By: Relevance
“…Related work has reported decreased oxygen consumption in Daphnia magna following exposure to UOG wastewater (Blewett et al, 2017b), as well as decreased heart rate and reduced metabolic rate in zebrafish larvae (Folkerts et al, 2017). These laboratories mirror many of the effects observed in epidemiological studies, including increased (Stacy et al, 2015; Walker Whitworth et al, 2018; Hill, 2014) or decreased (McKenzie et al, 2014) prevalence of low birth weights and physician-recorded high-risk pregnancies (Casey et al, 2016). Other work has reported increased atmospheric carbon disulfide near UOG operations, which has the ability to dysregulate normal glucose metabolism and may be a causative pathway through which UOG operations may influence metabolic health (Rich et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Related work has reported decreased oxygen consumption in Daphnia magna following exposure to UOG wastewater (Blewett et al, 2017b), as well as decreased heart rate and reduced metabolic rate in zebrafish larvae (Folkerts et al, 2017). These laboratories mirror many of the effects observed in epidemiological studies, including increased (Stacy et al, 2015; Walker Whitworth et al, 2018; Hill, 2014) or decreased (McKenzie et al, 2014) prevalence of low birth weights and physician-recorded high-risk pregnancies (Casey et al, 2016). Other work has reported increased atmospheric carbon disulfide near UOG operations, which has the ability to dysregulate normal glucose metabolism and may be a causative pathway through which UOG operations may influence metabolic health (Rich et al, 2016).…”
Section: Discussionmentioning
confidence: 64%
“…Timing of an environmental stressor may matter for maternal mental health and birth outcomes (Glynn et al, 2001) and while our exposure metric was time-varying, we were unable to assess the effects of trimester-specific exposures. Whitworth et al (2018) recently examined trimester-specific and phase-specific associations between UNGD and risk of preterm birth in Texas, finding the strongest associations with exposures in the first and second trimesters. While we stratified analyses by receipt of Medical Assistance, an indicator of low family income, research suggests that risk factors for and vulnerability to poor antenatal mental health may differ by race/ethnicity (Biaggi et al, 2016;Mukherjee et al, 2016).…”
Section: Limitationsmentioning
confidence: 99%
“…Others caution that negative externalities may exist for populations living nearby in the form of reduced quality of life (Fisher et al, 2018;Jacquet et al, 2018;Perry, 2013), migraine headache and fatigue (Tustin et al, 2017), asthma exacerbations (Rasmussen et al, 2016), and worse cardiovascular health (McKenzie et al, 2019). Studies in Colorado, Oklahoma, and Pennsylvania have found associations between residential proximity to UNGD and adverse birth outcomes (Casey et al, 2016;Currie et al, 2017;Hill, 2018;Janitz et al, 2019;McKenzie et al, 2014;Stacy et al, 2015;Whitworth et al 2017bWhitworth et al , 2018. While Currie et al, 2017 andHill, 2018 implemented analytic strategies designed to support causal inference, no large epidemiologic studies have attempted to disentangle the complex pathways that may link UNGD to adverse birth outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have focused on economic and environmental impacts of shale development (Joskow 2013;Kelsey, Partridge, and White 2016;Paredes, Komarek, and Loveridge 2015;Tsvetkova and Partridge 2016;White 2012). Others have examined the health consequences of increasing O&G production through fracking (Bunch et al 2014;Colborn et al 2013;Elliott et al 2016;McKenzie et al 2012;Mitka 2012;Werner et al 2015;Whitworth, Marshall, and Symanski 2018). Fewer studies examine social changes brought on by resource extraction in the United States (Brown, Dorius, and Krannich 2005;Komarek 2018;Perry 2012;Ruddell and Ortiz 2015;Schafft Borlu, and Glenna 2013;Smith, Krannich, and Hunter 2001) and fewer still have focused specifically on family outcomes (Betz and Snyder 2017;Kearney and Wilson 2017).…”
Section: Introductionmentioning
confidence: 99%